Smart Weather Monitoring System Using ESP32 and IoT - Saurav Jagtap; Shreyas Yadav; Shivam Yewale; Devang Dudhane; Prakash Kumar (International Journal of Electrical and Communication Engineering Technology, 2025)
The increasing unpredictability of climate conditions necessitates an efficient and real-time weather monitoring system. The following paper describes an IoT weather monitoring system using the ESP32 microcontroller, connected to various environmental sensors to gather and process atmospheric information. The system uses a DHT11 sensor to measure temperature and humidity, an MQ135 gas sensor for measuring air quality, and a PM2.5 sensor to measure the level of particulate matter. The ESP32 web server acts as the processor, forwarding accumulated information to a TFT display for real-time visualization and to the Blynk IoT platform for remote monitoring. The application of WiFi connectivity enables easy data transfer, and users can view weather data through a cloud-based app. The system aims to be low-cost, energy-effective, and scaleable to accommodate various environmental requirements, e.g., smart agriculture, air pollution control in cities, and disaster prediction. Incorporation of IoT enhances the usability and accessibility of the system via remote monitoring. Experiments results indicate that the system effectively acquires and presents live environmental parameters with the advantage of being a dependable method of weather monitoring. Future expansion can also entail the incorporation of AI algorithms for predictive analytics and anomaly detection to further improve the efficacy of the system. This research contributes to the development of smart environmental monitoring solutions that can support climate resilience and sustainability interventions.
Keywords: Air quality; BLYNK; DHT11; ESP32; Environmental monitoring; IOT; PM2.5 Sensor; Smart Agriculture; Weather Monitoring; remote sensing